2015
DOI: 10.1159/000437249
|View full text |Cite
|
Sign up to set email alerts
|

A Case of Multiple Spontaneous Keloid Scars

Abstract: Keloid scars result from an abnormal healing response to cutaneous injury or inflammation that extends beyond the borders of the original wound. Spontaneous keloid scars forming in the absence of any previous trauma or surgical procedure are rare. Certain syndromes have been associated with this phenomenon, and few reports have discussed the evidence of single spontaneous keloid scar, which raises the question whether they are really spontaneous. Here, we present a 27-year-old mentally retarded single female w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0
8

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 178 publications
(29 citation statements)
references
References 12 publications
0
21
0
8
Order By: Relevance
“…Later in life, he developed a keloid over the surgical insertion site of a pacemaker [15]. We also reported that a syndromic 27-year-old female who has mental retardation along with orbital hypertelorism, a broad nasal bridge, high arched palate, and repaired cleft lip developed sudden widespread extensive keloids over multiple sites of her body [16].…”
Section: Genetic Associationmentioning
confidence: 66%
“…Later in life, he developed a keloid over the surgical insertion site of a pacemaker [15]. We also reported that a syndromic 27-year-old female who has mental retardation along with orbital hypertelorism, a broad nasal bridge, high arched palate, and repaired cleft lip developed sudden widespread extensive keloids over multiple sites of her body [16].…”
Section: Genetic Associationmentioning
confidence: 66%
“…They may result from a cutaneous injury to the reticular dermis [ 2 ], such as surgery or mechanical trauma. Rarely, they may occur spontaneously [ 3 ]. Although the mechanism of keloid formation is not known with certainty, they are characterized by increased fibroblasts and collagen formation, new blood vessel growth and the presence of upregulated proinflammatory factors [ 2 , 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Surgical excision of keloids as sole therapy is associated with recurrence rates as high as 80% [ 3 ], 65–99% [ 7 ] and 45–100% [ 8 ]. Consequently, a wide range of treatments have been used to treat keloid scars, including silicon sheeting, topicals, intralesional corticosteroid injections, cryotherapy, lasers and post-keloidectomy radiation therapy [ 4 , 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…1,2 These fibrous growths result from a connective tissue response to trauma, burns, surgery, or inflammation, and seems occasionally occur spontaneously. 3,4 Psychosocial problems often occur due to cosmetic issues and contracture as complications from keloid.…”
Section: Introductionmentioning
confidence: 99%
“…Basic fibroblast growth factor (bFGF) inhibits collagen production and stimulates collagen degradation. 1 A real challenge is faced in the therapy of keloid since no treatment is highly effective for this condition to date. There are several therapies for the treatment of keloid, such as laser, silicone gel, excision, interferon, corticosteroid intralesional injection, radiation, cryotherapy, and 5-fluorouracil injection, or combination.…”
Section: Introductionmentioning
confidence: 99%